Novel antimicrobial activities of self-nanoemulsifying drug delivery system (SNEDDS) ethyl acetate fraction from Garcinia mangostana L. peels against Staphylococcus epidermidis: Design, optimization, and in vitro studies - Liza Pratiwi (Journal of Applied Pharmaceutical Science, 2021)
The purposes of this study were to determine the comparison of Tween 80, PEG 400, and Virgin Coconut Oil to produce the optimal self-nanoemulsifying drug delivery system (SNEDDS) of the ethyl acetate fraction mangosteen peels and to analyze the effectiveness of the optimal SNEDDS against Staphylococcus epidermidis. The optimal SNEDDS was obtained with the Design-Expert software and simplex lattice design method with various combinations, namely Tween 80, PEG 400, and Virgin Coconut Oil. The research method begins with the extraction process using the maceration method using ethanol solvent, and then, the ethanol extract was fractionated with ethyl acetate solvent. The optimal SNEDDS was evaluated for transmittance value, pH, emulsification time, particle size, zeta potential, and their in vitro activity against S. epidermidis. The optimal SNEDDS obtained was a combination of Tween 80:PEG 400:Virgin Coconut Oil with a composition ratio of 4.98:1.02:1. Based on the evaluation, the transmittance value was 72.74% ± 1.08%, the pH was 6.48 ± 0.03, emulsification time was 4.83 sec ± 0.95 sec, the average droplet size was 77.3 nm ± 0.232 nm, and the zeta potential value was −8.29 ± 0.04 mV. The optimal SNEDDS of ethyl acetate fraction of mangosteen peels had a higher activity against S. epidermidis than the fraction without SNEDDS.
Keywords: SNEDDS, Garcinia mangostana, Staphylococcus epidermidis, simplex lattice design.